2013
DOI: 10.1159/000342143
|View full text |Cite
|
Sign up to set email alerts
|

Non-Human Predator Interactions with Wild Great Apes in Africa and the Use of Camera Traps to Study Their Dynamics

Abstract: The slow life histories of great apes (hereafter ‘apes’) combined with a growing inventory of predation incidents suggest that apes may be strongly affected by direct predation, as well as by predation risk. Predation risk may shape and increase behavioural flexibility by forcing individuals to adapt their behaviour to predator patterns. Forest leopards are an apex predator of primates in African rain forests and may represent a significant risk to ape populations. More field data are needed to further elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…A preference for foraging in denser habitats must therefore contribute. This preference has consequences for predation risk [96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preference for foraging in denser habitats must therefore contribute. This preference has consequences for predation risk [96].…”
Section: Discussionmentioning
confidence: 99%
“…For primates, Ross [97][99] showed that closed habitats apparently select for slow reproductive rates, even after the effects of body mass and environmental factors, like rainfall, have been taken into account. The denser forests occupied by gorillas are predicted to provide greater protection, especially from predation by leopards [96]. Because of their greater terrestriality gorillas are at a greater risk of predation, although their larger body masses and group cohesion offer some protection.…”
Section: Discussionmentioning
confidence: 99%
“…Leopards are the only known predator of gorillas aside from humans . Leopards are found in most areas where western gorillas occur, yet they have not been observed in either the Virungas or Bwindi for decades .…”
Section: Hypotheses For Variation In Social Organizationmentioning
confidence: 99%
“…It has great potential to provide unique and valuable data on the impacts of conservation threats [71], sociodemographics [23], behavioural plasticity [32,55,3], disease mapping and screening [9], species interactions [23], habitat use [53,24], feeding ecology [24,51,59], activity patterns [32,55], and ranging patterns [48].…”
Section: Monitoring In Ecology Todaymentioning
confidence: 99%